Brooklyn's finest [videorecording (DVD)] - Fuqua, Antoine; Martin, Michael C. (Screenwriter); Zarvos, Marcelo; Gere, Richard, 1949-; Cheadle, Don; Hawke, Ethan, 1970-; Snipes, Wesley; Barkin, Ellen, 1954-; D'Onofrio, Vincent; Patton, Will; Taylor, Lili; O'Byrne, Brian F.; et al. (Overture Films ; Distributed by Anchor Bay Entertainment, 2010)
After having endured extremely different career paths, the lives of three disheartened Brooklyn police officers will collide with destiny when they all wind up at the same fatal crime scene.